2019
DOI: 10.26694/repis.v5i0.8158
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Institutions of Elderly Persons in the Public System in the State of Piauí in 2017

Abstract: Objective: to characterize the profile of hospital admissions of the elderly in the public system of Piauí in the year 2017. Methodology: cross-sectional and retrospective study, based on the data available in the Information System on Morbidity of the Ministry of Health in the page of the Department of Information Technology of SUS (DATASUS). Results: The elderly were in the age group of 80 years or older, were male and 24.7% had diseases of the circulatory system. The main cause of mortality was diseases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…1 Congenital syphilis (CS) has the bacterium Treponema Pallidum as an etiologic agent, and this infection is mandatory, as it is responsible for unfavorable outcomes such as fetal or perinatal death, prematurity, low birth weight, neurological injuries, among other sequelae. 2 When syphilis appears soon after birth, or before the first two years of life, it is called early CS, equivalent to acquired secondary syphilis. When it begins after two years of life, it is called late CS and is equivalent to late syphilis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Congenital syphilis (CS) has the bacterium Treponema Pallidum as an etiologic agent, and this infection is mandatory, as it is responsible for unfavorable outcomes such as fetal or perinatal death, prematurity, low birth weight, neurological injuries, among other sequelae. 2 When syphilis appears soon after birth, or before the first two years of life, it is called early CS, equivalent to acquired secondary syphilis. When it begins after two years of life, it is called late CS and is equivalent to late syphilis.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, only in 2016, 19,846 cases of CS were diagnosed, and 185 deaths in children under the age of one year were declared in the mortality information system, verifying that in ten years, there was a considerable increase in the rate of infant mortality due to CS. 2 CS is a disease that can be prevented through A significant number of syphilis in adolescents was also identified, which can be inferred from the lack of health education in this age group, demonstrated by the early and unprotected initiation of sexual life. 4 With regard to the level of education, it was observed that there was a high frequency in women with, at most, incomplete elementary education, a situation that becomes a major dilemma for public health, because for the population to be able to promote adequate prevention, the awareness of the disease is necessary.…”
Section: Introductionmentioning
confidence: 99%